Minds, Bodies, Machines, 1770-1930
XI, 230 p.
Keywords: It is during the nineteenth-century, the age of machinery, that we begin to witness a sustained exploration of the literal and discursive entanglements of minds, bodies, machines. This book explores the impact of technology upon conceptions of language, consciousness, human cognition, and the boundaries between materialist and esoteric sciences.